Unmodified multi-wall carbon nanotubes in polylactic acid for electrically conductive injection-moulded composites. (December 2017) - Rivière, Pauline; Nypelö, Tiina E; Obersriebnig, Michael; Bock, Henry; Müller, Marcus; Mundigler, Norbert; Wimmer, Rupert
Tailoring the properties of natural polymers such as electrical conductivity is vital to widen the range of future applications. In this article, the potential of electrically conducting multi-wall carbon nanotube (MWCNT)/polylactic acid (PLA) composites produced by industrially viable melt mixing is assessed simultaneously to MWCNT influence on the composite's mechanical strength and polymer crystallinity. Atomic force microscopy observations showed that melt mixing achieved an effective distribution and individualization of unmodified nanotubes within the polymer matrix. However, as a trade-off of the poor tube/matrix adhesion, the tensile strength was lowered. With 10 wt% MWCNT loading, the tensile strength was 26% lower than for neat PLA. Differential scanning calorimetric measurements indicated that polymer crystallization after injection moulding was nearly unaffected by the presence of nanotubes and remained at 15%. The resulting composites became conductive below 5 wt% loading and reached conductivities of 51 S m −1 at 10 wt%, which is comparable with conductivities reported for similar nanocomposites obtained at lab scale.